Development of Kotak Saran for Unit of Measurement Learning in SLB Negeri 2 Sawahlunto - Paramuditha, Widi Kumara Jaga; Padri, Maizal; Handayani, Fitri; Harianti, Yutri; Rahmahtrisilvia , Rahmahtrisilvia; Tsaputra, Antoni; Irdamurni, Irdamurni; Iswari, Mega (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
This research was motivated by the lack of innovative teaching tools in special education settings, one of which is learning the conversion of units of measurement. The research was conducted at SLB Negeri 2 Sawahlunto with the target of intellectual   disability students who face challenges in understanding math concepts related to units of measurement. This research aims to develop learning media in the form of Kotak Saran (Unit of Measurement Conversion). Using research and development methods with 4D design. The subject of this research and development trial was by related experts such as media experts, tools, and learning for students with disabilities. As well as a practicality test by an educator and a student of intellectual disability. The data collection tool is a questionnaire instrument for the validity of the Kotak Saran media and a response instrument for the assessment of the Kotak Saran media. The data analysis technique used is descriptive data analysis technique. The results of this study indicate that the Kotak Saran learning media is useful and feasible as a learning media in the conversion of units of measurement with the acquisition of a validation value of 92.40% and a practicality test of 82.5%. The final form of this product is in the form of learning media packaged in the form of an android application so that it can be opened anywhere and anytime via an android smartphone.